Case studies in abdominal and pelvic imaging - Joarder, Rita (Springer, 2011)
Case Studies in Abdominal and Pelvic Imaging presents 100 case studies, covering both common every-day conditions of the abdomen and pelvis, as well as less common cases that junior doctors and radiologists in training should be aware of. Compiled by experts in the field, Case Studies in Abdominal and Pelvic Imaging uses the most up-to-date and high quality images, including plain films, CT scans, MRI scans and the occasional nuclear medicine image where relevant. Each case is presented in a pedagogical style, with 1-4 images and accompanying questions, followed by answers and further relevant images.This is then augmented by an explanation of the imaging and key teaching points with references for further reading, making this book a valuable learning guide in an accessible form.